Anemia among Adolescent Girls: Its Association with Protein and Iron Intake - Jumiyati Jumiyati; Arie Krisnasary; Risda Yulianti; Tetes Wahyu Witradharma (Universitas Airlangga, 2023)
Adolescence is a time of physical and psychological growth as people transition to adulthood, and proper nutrition is essential for this process. Anemia, a condition characterized by a lack of red blood cells or hemoglobin, is the most common health issue among young women. In 2018, the prevalence of anemia was higher in women (27.2%) than in men (20.3%), and particularly high (32%) in the 15-24 age group. The purpose of this study was to investigate the prevalence of anemia among teenage women in a rural area . The study used a cross-sectional design and included 112 middle school female students in Rejang Lebong Regency. The data was collected using survey questionnaire and a semi-quantitative food frequency questionnaire to assess factors such as knowledge, the intake of calorie, protein, vitamin C, and iron. Correlation analysis and multiple linear regression were used to analyze the relations between these variables and anemia status. The correlation analysis showed that knowledge, calorie intake, and vitamin C were not significantly correlated with anemia (p values 0.378, 0.563 and 0.087, respectively). However, there was a significant correlation between iron and protein intake with the occurrence of anemia (p values 0.000 and 0.030).